Developing neurites from mouse basal forebrain gonadotropin‐releasing hormone neurons use Sonic hedgehog to modulate their growth. Issue 68 (19th May 2018) - Tan, C.L.; Sheard, P.W.; Jasoni, C.L.
Abstract: Hypothalamic gonadotropin‐releasing hormone (GnRH) neurons are required for fertility in all mammalian species studied to date. GnRH neuron cell bodies reside in the basal forebrain, and most extend long neurites in the caudal direction to terminate at the median eminence (ME), the site of hormone secretion. Using in vitro neurite growth assays, histological methods, and genetic deletion strategies in mice we have analysed the role of the morphogen and neurite growth and guidance molecule, Sonic hedgehog (Shh), in the growth of GnRH neurites to their target. Immunohistochemistry revealed that Shh was present in the basal forebrain, the preoptic area (POA) and mediobasal hypothalamus (MBH) at gestational day 14.5 (GD 14.5), a time when GnRH neurites grow towards the ME. Furthermore, in situ hybridization revealed that mRNA encoding the Shh receptor, Smoothened (Smo), was present in GnRH neurons from GD 15.5, when the first GnRH neurites are extending towards the MBH. In vitro neurite growth assays using hypothalamic explants from GD 15.5 fetuses in 3‐D collagen gels showed that Shh was able to significantly stimulate GnRH neurite outgrowth. Finally, genetic deletion of Smo specifically from GnRH neurons in vivo, using Cre‐ loxP technology, resulted in a significant decrease in GnRH neurites innervating the ME. These experiments demonstrate that GnRH neurites use Shh for their neurite development, provide further understanding of the mechanisms by which GnRH nerve terminals arrive at their site of hormone secretion, and identify an additional hypothalamic neuronal population for which Shh/Smo signaling is developmentally important.